(untitled) (Biological Sciences - PJSIR, 1999)
The present paper is. based on studies carried out for replacement of HN03 using oxo trinuclear complexes of Ru, Rh, Nb, Mo and Fe with dicarboxylic acids and the study of adipic acid preparation reaction mechanism.